2004
DOI: 10.1128/aem.70.9.5081-5088.2004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Complex Nutrient Source on Growth of and Curvacin A Production by Sausage Isolate Lactobacillus curvatus LTH 1174

Abstract: ) was used to fit the data describing growth and bacteriocin production. Both cell growth and bacteriocin activity were influenced by changes in the complex nutrient source concentration. Standard MRS medium clearly limited the growth of L. curvatus LTH 1174. Higher nutrient concentrations, up to a certain degree, led to improved growth, a higher attainable biomass concentration, and a higher bacteriocin activity in the supernatant. A lower concentration of complex nutrient source caused severe growth inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Depletion of another nutrient, cell density, or the presence of toxic products may probably induce this phase (64). Growth of lactic acid bacteria is inhibited not only by the production of metabolites such as lactic acid but also by limited concentrations of indispensable nutrients present in the MRS medium (61). It has been reported that a high level of lactic acid was one of the most likely explanations for the shortened stationary-phase persistence in Streptococcus pyogenes batch culture (65).…”
Section: Resultsmentioning
confidence: 99%
“…Depletion of another nutrient, cell density, or the presence of toxic products may probably induce this phase (64). Growth of lactic acid bacteria is inhibited not only by the production of metabolites such as lactic acid but also by limited concentrations of indispensable nutrients present in the MRS medium (61). It has been reported that a high level of lactic acid was one of the most likely explanations for the shortened stationary-phase persistence in Streptococcus pyogenes batch culture (65).…”
Section: Resultsmentioning
confidence: 99%
“…The max , , and K d of LIS R were determined independently; the other parameters were set as for the Listeria monoculture and LIS S . Upon repetition, the coefficients of variation of the parameters are generally lower than 10%, with the exception of k inact for which 25% can be observed (13,17,(20)(21)(22).…”
mentioning
confidence: 99%
“…Compared with the results of Lobas et al and Kanari et al, the period of the fermentation process was shortened, and higher gellan gum production (14.75 g liter Ϫ1 ) was obtained in a 30-liter fermentor under optimal conditions. Various mathematical models have been proposed for the kinetics of microbial growth and product formation with other strains (2,6,31). For extracellular polysaccharide production, the logistic and Luedeking-Piret equations, developed originally for the formation of lactic acid (20), have been proposed to describe the time courses of product formation, substrate consumption, and cell growth (7,18,32), because those models are substantially more accurate and convenient than other models that have been reported.…”
mentioning
confidence: 99%